The Evaluation for Accuracy of Non-destructive Testing (NDT) in Ultrasonic Inspection on Stainless Steel Material by Ultrasonic Testing Thickness Measurement - Iskandar, Nurhusnina; M Yusuf, Ir. Dr. Eliza (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this paper, the thickness of Stainless Steel plates was measured and analyzed using an ultrasonic testing thickness measurement using pulse-echo method. Factors in thickness measurement had a particular influence on the thickness measured on coupling agent, blasting effect, and different types of probes. The accuracy of UTTM technique was compared with ruler and digital vernier calliper. For effectiveness, the surface of samples were also cleaned with sand blasting process to observe the ageing effect on the specimens. The results of all 30 days revealed that, of all the devices used to measure thickness, the vernier calliper has the best percentage of accuracy (close to 100%), while the UTTM by double crystal probe has the highest (98%) when compared to single crystal probe. To summarise, the UTTM method can measure the thickness of any material in any circumstance, and the results have proven to be as accurate as a ruler and a Vernier calliper. Even when access is not accessible from both sides, UTTM produces the closest answer to the actual measurement.